2017
DOI: 10.1186/s13047-017-0238-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a running task on muscle shear elastic modulus of posterior lower leg

Abstract: BackgroundMedial tibial stress syndrome (MTSS) is one of the most common causes of exercise-related leg pain in runners. Because stopping training due to pain from MTSS could decrease the athlete’s competitiveness, it is necessary to construct MTSS prevention and treatment programs. However, the effect of running, which is believed to cause MTSS, on shear elastic modulus of the posterior lower leg is unclear. Therefore, the purpose of this study was to investigate the effect of 30 min of running on shear elast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 31 publications
3
15
2
Order By: Relevance
“…Some 14 weeks of resistance training intervention resulted in a 16% increase in triceps surae aponeurosis stiffness ( Albracht and Arampatzis, 2013 ). However, inconsistent with our results, 20 healthy participants were recruited to measure the elastic modulus of the calf muscles using shear wave elastography at the beginning and end of a 30-min running task, and they found no significant change in the LG and MG after the exercise ( Ohya et al, 2017 ). In that study, the participants were asked to perform a 30-min running task.…”
Section: Discussioncontrasting
confidence: 98%
“…Some 14 weeks of resistance training intervention resulted in a 16% increase in triceps surae aponeurosis stiffness ( Albracht and Arampatzis, 2013 ). However, inconsistent with our results, 20 healthy participants were recruited to measure the elastic modulus of the calf muscles using shear wave elastography at the beginning and end of a 30-min running task, and they found no significant change in the LG and MG after the exercise ( Ohya et al, 2017 ). In that study, the participants were asked to perform a 30-min running task.…”
Section: Discussioncontrasting
confidence: 98%
“…Stiffness of the gastrocnemius reportedly has a strong correlation with plantar fasciitis [23]. Moreover, patients with a history of medial tibial stress syndrome had stiff FDLs [17] and increased stiffness of the FDL after running [16]. These results are similar to those of the our study, which show an increase in the stiffness of muscles related to running injuries.…”
Section: Discussionsupporting
confidence: 90%
“…Long distance running tends to decrease the height of the medial longitudinal arch, and to reduce arch exibility [14,15]. Moreover, the stiffness of the dynamic stabilizers of the arch, such as the tibialis posterior and the FDL, is increased after running [16,17]. However, the effects of the structure and exibility of the arch on changes in muscle stiffness after running are unclear.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is speculated that excessive motion of the rearfoot leads to higher eccentric contraction level of these muscles and produces higher stress on the medial tibia. A previous study showed that running for 30 min increased the tibialis posterior and flexor digitorum longus stiffness [28]. Also, runners with an MTSS history demonstrated higher tibialis posterior and flexor digitorum longus stiffness than that in no MTSS history [29].…”
Section: Discussionmentioning
confidence: 86%